World League volleyball 2016: Counter-attack is a discriminant analysis factor - Joao, P. V.; Kraak, W.; Lee, M.; Vaz, L. (World Congress of Performance Analysis of Sport XI - Alicante, 16th - 18th November 2016, 2016)
Video ab 2:32:04